Cyclooxygenase-2 Upregulated by Temozolomide in Glioblastoma Cells Is Shuttled In Extracellular Vesicles Modifying Recipient Cell Phenotype - Lombardi, Francesca; Augello, Francesca Rosaria; Artone, Serena; Ayroldi, Emira; Giusti, Ilaria; Dolo, Vincenza; Cifone, Maria Grazia; Cinque, Benedetta; Palumbo, Paola (Frontiers in Oncology, 2022)
Temozolomide (TMZ) resistance is frequent in patients with glioblastoma (GBM), a tumor characterized by a marked inflammatory microenvironment. Recently, our group reported evidence that cyclooxygenase-2 (COX-2) is upregulated in TMZ-resistant GBM cells treated with high TMZ concentrations. Moreover, the COX-2 activity inhibition with NS398, the specific enzyme inhibitor, significantly counteracted TMZ-resistance of GBM cells. Extracellular vesicles (EV) secreted by GBM cells, creating a communication network able to modulate the tumor microenvironment (TME), are crucial mediators affecting the surrounding recipient cell phenotype and behavior. This work aimed to verify whether TMZ, at low and clinically relevant doses (range 5-20 µM), was still able to induce COX-2 overexpression in TMZ-resistant T98G cells and explore if secreted EV contained and delivered COX-2 to recipient cells. COX-2 inhibitors (COXIB), Celecoxib (CXB), or NS398, alone or combined with TMZ, were also investigated. Our results indicated that TMZ, even at low, clinically relevant doses, dose-dependently upregulated COX-2 in T98G cells. Expression of β-catenin and O6-methylguanine-DNA methyltransferase (MGMT), both strictly related to COX-2 activity and associated with GBM chemoresistance followed a behaviour similar to that of COX2. Treatment with CXB or NS398 significantly counteracted TMZ-induced COX-2 expression, confirming the crucial role of the COX-2/PGE2 system in TMZ-resistance. The specificity of COXIB was verified on U251MG, COX-2 null GBM cells. Western blotting analysis of EV released by T98G cells highlighted the presence of COX-2, which followed the same trend as intracellular levels, increasing in a dose-dependent way in EV derived from TMZ-treated cells and decreasing in those released by cells exposed to combined treatments (COXIB+TMZ). The high levels of COX-2 in the EV secreted by TMZ-treated T98G cells were associated with their ability to induce a pro-tumor M2-like phenotype in the human macrophage cell line U937, used as recipient cells. This effect was prevented by treatment of T98G cells with combination of COXIB+TMZ as demonstrated by the assay of TGF-1, a hallmark of the transition in M2 macrophage state. These data confirm the crucial role of COX-2 in TMZ-resistance and suggest a role for this enzyme in EV-mediated intercellular communications, opening the way for novel pharmacological strategies.